Overcoming the Limitations of MXene Electrodes for Solution‐Processed Optoelectronic Devices. Issue 41 (14th September 2022) - Zhou, Huanyu; Han, Shin Jung; Lee, Hyeon‐Dong; Zhang, Danzhen; Anayee, Mark; Jo, Seung Hyeon; Gogotsi, Yury; Lee, Tae‐Woo
Abstract: MXenes constitute a rapidly growing family of 2D materials that are promising for optoelectronic applications because of numerous attractive properties, including high electrical conductivity. However, the most widely used titanium carbide (Ti3 C2 T x ) MXene transparent conductive electrode exhibits insufficient environmental stability and work function ( WF ), which impede practical applications Ti3 C2 T x electrodes in solution‐processed optoelectronics. Herein, Ti3 C2 T x MXene film with a compact structure and a perfluorosulfonic acid (PFSA) barrier layer is presented as a promising electrode for organic light‐emitting diodes (OLEDs). The electrode shows excellent environmental stability, high WF of 5.84 eV, and low sheet resistance R S of 97.4 Ω sq −1 . The compact Ti3 C2 T x structure after thermal annealing resists intercalation of moisture and environmental contaminants. In addition, the PFSA surface modification passivates interflake defects and modulates the WF . Thus, changes in the WF and R S are negligible even after 22 days of exposure to ambient air. The Ti3 C2 T x MXene is applied for large‐area, 10 × 10 passive matrix flexible OLEDs on substrates measuring 6 × 6 cm. This work provides a simple but efficient strategy to overcome both the limited environmental stability and low WF of MXene electrodes for solution‐processable optoelectronics. Abstract : Recently, various applications of MXenes have been intensively explored, except for optoelectronics, in which poor environmental stability severely impedes their practical application. This work provides a simple but effective approach to develop an environmentally stable MXene electrode that exhibits a high work function of 5.84 eV and distinguished solution processibility as the electrode for large‐area organic light‐emitting diodes.